2018
DOI: 10.1093/jmcb/mjy069
|View full text |Cite
|
Sign up to set email alerts
|

Dppa3 is critical for Lin28a-regulated ES cells naïve–primed state conversion

Abstract: Lin28a is a pluripotent factor that promotes somatic cell reprogramming. Unlike other pluripotent factors, Lin28a expression is transient and accumulated in primed embryonic stem (ES) cells, but its exact function and mechanism in the conversion of ES cells from naïve to primed state remain unclear. Here, we present evidence for Dppa3, a protein originally known for its role in germ cell development, as a downstream target of Lin28a in naïve–primed conversion. Using rescue experiment, we demonstrate that Dppa3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Of note, other epigenetic pathways such as suppression of H3K9me2 by MAD2L2 as well as eRNA dependent enhancer regulation also have been shown to positively regulate the transcription of Dppa3 109,112 , and silencing of Dppa3 has been shown to depend on Lin28a, TBX3, and intact DNA methylation maintenance [113][114][115] . Taken together, these findings suggest that Dppa3 is regulated by a complex network of pathways to ensure proper timing of its expression in order to prevent unwanted global DNA demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, other epigenetic pathways such as suppression of H3K9me2 by MAD2L2 as well as eRNA dependent enhancer regulation also have been shown to positively regulate the transcription of Dppa3 109,112 , and silencing of Dppa3 has been shown to depend on Lin28a, TBX3, and intact DNA methylation maintenance [113][114][115] . Taken together, these findings suggest that Dppa3 is regulated by a complex network of pathways to ensure proper timing of its expression in order to prevent unwanted global DNA demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, SCD1 is a lipid metabolic enzyme involved in lipogenesis, and proteins associated with fatty acid metabolism were reported to be highly expressed in naive mESCs (Taleahmad et al 2015(Taleahmad et al , 2018. Similarly, Dppa3 and Gdf3 were known to be important for naive pluripotency Sang et al 2019). Altogether, this highlights the differential interactive networks in which the cluster-specific putative regulatory elements result in differential expression of the respective target genes.…”
Section: Deconstruction Of Heterogeneity In Mescs Under Distinct Cellmentioning
confidence: 74%
“…The AP staining assays showed that AP activity and colony size decreased significantly in the OEOCT4- sh LIN28A2 group without DOX ( Figure 2F ). Based on AP staining assays ( Sang et al, 2019 ), colonies can be classified into three shapes: i.e., typical primed diffuse-shape, compact dome-shape, and mixed-shape. Compact dome-shaped colonies in the OEOCT4- sh NC group accounted for 60% of total colonies in this group, while compact dome-shaped colonies in the OEOCT4- sh LIN28A2 group accounted for ~50%; however, the total number of colonies in the OEOCT4- sh LIN28A2 group decreased significantly and colonies in the OEOCT4- sh LIN28A2 group basically disappeared ( Figure 2G ).…”
Section: Resultsmentioning
confidence: 99%
“…LIN28A can regulate the naïve to primed state conversion by regulating stem cell metabolism in induced pluripotent stem cells (iPSCs) ( Zhang et al, 2016 ). Knockdown of LIN28A promotes the transformation of embryonic stem cells (ESCs) into the naïve state ( Chandrasekaran et al, 2017 ; Kumar et al, 2014 ; Marks et al, 2012 ), and LIN28A regulates pluripotent state transformation in mouse ESCs by inhibiting DPPA3 expression ( Sang et al, 2019 ). However, few studies have explored LIN28A in porcine iPSCs (piPSCs) and the mechanism underlying LIN28A functions in piPSCs remains unclear.…”
Section: Introductionmentioning
confidence: 99%